The protein intake of trained bodybuilders is concentrated in lunch and dinner - Gabriela Rosa Gonçalves; Edilson Tadeu Ferreira Furtado; Isabela Simões de Boucherville Pereira; João Paulo Lima de Oliveira; Wilson César de Abreu (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2023)
Regular protein intake throughout the day can contribute to maximising protein synthesis and improve recovery and muscle mass gain. The objective of this study was to evaluate the dietary intake and the distribution of protein, carbohydrate, lipid and energy intakes of trained bodybuilders. Twelve men with experience in resistance training participated in the study. Body composition was determined by octapolar bioimpedance. Food intake was assessed using five 24-hour food recall schedules. The subjects presented the following characteristics: Age = 25.2 ± 3.4 years; Height = 179.5 ± 4.6 cm; Weight = 84.9 ± 8.7 kg; Body Fat = 14.7 ± 5.6% and Fat Free Mass = 85.3 ± 5.6%. The average time of weight training practice was 5.9 ± 3.1 years, with a weekly frequency of 5.0 ± 0.6 workouts and each session lasting an average of 64.2 ± 17.8 minutes. The average caloric intake was 2201 ± 223 kcal which represented 26.2 ± 6.0 kcal/kg. Only 33.3% of the individuals had adequate energy intake. The participants had a mean daily consumption of 1.6 ± 0.5 g/kg/day for proteins, 2.9 ± 0.8 g/kg/day for carbohydrates and 0.9 ± 0.4 g/kg/day for fat. The percentage of adequacy was 58.3%, 50%, and 91.7% for carbohydrates, proteins, and fat, respectively. Protein consumption was irregular throughout the day, being concentrated at lunch (52.2 ± 17.8 g) and dinner (40.2 ± 20.5 g). We conclude that the individuals consumed a diet with low energy content and irregular distribution throughout the day, especially of protein. Thus, the results indicate that the dietary intake of the volunteers can be improved expressively.